PM2.5-bound biogenic secondary organic aerosol tracers over a regionally representative site in central India: Characteristics and sources. (1st February 2023) - Nirmalkar, Jayant; Sunder Raman, Ramya; Deshmukh, Dhananjay K.; Haque, MD. Mozammel
Abstract: Biogenic secondary organic aerosol (BSOA) in PM2.5 over Bhopal, central India were quantified. Fine particles were collected on Teflon filters for measuring PM2.5 mass and on quartz fiber filter for organic carbon (OC), elemental carbon (EC), and BSOA tracers, including oxidation products of isoprene, monoterpene and sesquiterpene between November 2017 and May 2018. Isoprene SOA tracers were present in the highest mean concentration (86.5 ng m −3 ± 93.5 ng m −3 ) amongst all quantified tracers, accounting for 64% ± 23% of the BSOA tracers. Isoprene oxidation products, including C5 -alkene triols and 2-methyltetrols, and sesquiterpene oxidation products (β-caryophyllinic acid), were found to be the most abundant compound class over the study location. Correlations in the temporal variation of tracers of isoprene and monoterpene, with ozone (O3 ) suggested that photochemical oxidation influenced their concentrations over central India. The temporal variation of β-caryophyllinic acid and comparison with the previous suggested that their concentration was potentially influenced by biomass burning. Overall, the findings suggest that oxidation products of isoprene, monoterpene and sesquiterpene can be utilized to understand the characteristics and apportionment of BSOA sources over central India. Highlights: BSOA tracers at a regional site in Central India were characterized. Isoprene was the dominant contributor to SOA tracers. Ratio of α/β-pinene tracers suggested that SOA were freshly formed. Monoterpene SOA was predominantly produced by the oxidation of α-pinene. BSOA was impacted by atmospheric oxidation and biomass burning.